The Verbal and Non-verbal Communication in Professional Training of Border Guards - Indriksons, Alens (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The main objective of organizations is to achieve goals. Achieving goals is not possible without successful communication in work environment. Verbal and non-verbalcommunication plays an important role in border guards professional training. The present paper explores the nature of verbal and non - verbal communication in organization, problems in communication process between persons who are involved in it. The paper covers border guard’s skills related to communication which are defined in border guard’s professional standards. It is difficult to implement some of them in Border Guard because of special rules and services conditions. The paper deals with the situations of verbal and nonverbal communication in professional training process in State Border Guard College.